PRINSIP SURAT KUASA MUTLAK DALAM RAPAT UMUM PEMEGANG SAHAM LUAR BIASA - Rinaldy Ridwan Noor; Paramita Prananingtyas (STIH Putri Maharaja, 2020)
The absence of principles in an absolute power of attorney in attending the Extraordinary General Meeting of Shareholders (EGMS) will raises a legal problem. Each party may commit acts that are contrary to law or decency, at the time of the EGMS. The Limited Liability Company Law does not yet clearly stipulate the principles that must be applied in making an absolute power of attorney. The paper will first explain the legal basis for the EGMS and will explain the principles that must be applied in an absolute power of attorney. This study uses a normative juridical research method, by examining the problem based on relevant laws and regulations. The result shows that the legal basis for the implementation of the EGMS is Article 78 paragraph 1 of the Limited Liability Company Law. The principles that must be applied in an absolute power of attorney to attend the EGMS, namely; Absolute power must not be withdrawn by the Authorizer, absolute power is exercised for the benefit of the Power of Attorney, and absolute power is not contrary to decency and public order. Absolute power is only exercised when the authorizer has the obligation to carry out certain legal actions. It must be based on an agreement between parties and cannot be terminated due to death and other conditions of cancellation of a power of attorney. Furthermore, the power is permitted if there is a guaranteed legal-obligation and is included in the type of special power of attorney, so it has the same legal basis and power.